Improving Rates of Immediate Postoperative Intravesical Chemotherapy with Gemcitabine for Low-Grade Bladder Cancer: An Implementation Analysis. Issue 1 (5th January 2022) - Steinmetz, Alexis R.; Gantz, Jacob; Fiscella, Kevin; Messing, Edward M.
Abstract: Introduction: We sought to demonstrate how an implementation science framework can be used to increase rates of postoperative intravesical chemotherapy with gemcitabine in patients with low-grade, nonmuscle-invasive bladder cancer, thereby improving the quality of cancer care. Methods: An audit performed at 2 University of Rochester Medical Center hospitals involved in the SWOG S0337 trial identified low usage rates of postoperative intravesical chemotherapy once study accrual closed. The Consolidated Framework for Implementation Research guided an evaluation of barriers to adoption of this evidence-based practice. Methods employed included an online survey of urologists' perceptions of postoperative gemcitabine, face-to-face interviews with key stakeholders and direct observation of utilization processes. Subsequent implementation strategies were mapped to identified barriers; educational training for urologists and support staff and refining workflow processes were critical aspects of the intervention. Repeat usage audits measured practice change at 1 year. Results: The pre-intervention rate of appropriate use of intravesical gemcitabine was 11% at Strong Memorial Hospital and increased to 78% after 4 months and 88% after 12 months. The pre-intervention rate was 37% at Highland Hospital and increased to 82% after 4 months and 94% after 12 months. Over the period audited, 8 patients received gemcitabine who ultimately had nonlow-grade histology. Conclusions: Implementation science can be used to improve the impact of evidence-based findings in urological practice. The Consolidated Framework for Implementation Research has been used extensively in the literature and was adapted for postoperative intravesical chemotherapy with gemcitabine. This approach is feasible, generalizable, and results in durable practice change.